Czynniki warunkujące losy absolwentów studiów I stopnia - przykład województwa podkarpackiego = Factors Determining the Careers of Undergraduates - Illustradted by the Example of Podkarpackie Province - Humenny, Grzegorz; Grygiel, Paweł (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to introduce the factors determining the careers of undergraduates of first-cycle full-time studies from the area of Podkarpackie Province based on panel survey. The analysis shows that careers are shaped multistage and the core factor is the type of university and the determinants of its choice, the economic situation of students` families among the others. The more difficult the situation is the higher probability of starting work, it is less likely then to start work and studies, and the least likely to start only studying.
Keywords: szkolnictwo wyższe; losy absolwentów studiów wyższych; województwo podkarpackie